Expert Consensus Statement: Pediatric Drug-Induced Sleep Endoscopy. (October 2021) - Baldassari, Cristina M.; Lam, Derek J.; Ishman, Stacey L.; Chernobilsky, Boris; Friedman, Norman R.; Giordano, Terri; Lawlor, Claire; Mitchell, Ron B.; Nardone, Heather; Ruda, James; Zalzal, Habib; Deneal, Adrienne; et al.
Objective: To develop an expert consensus statement on pediatric drug-induced sleep endoscopy (DISE) that clarifies controversies and offers opportunities for quality improvement. Pediatric DISE was defined as flexible endoscopy to examine the upper airway of a child with obstructive sleep apnea who is sedated and asleep. Methods: Development group members with expertise in pediatric DISE followed established guidelines for developing consensus statements. A search strategist systematically reviewed the literature, and the best available evidence was used to compose consensus statements regarding DISE in children 0 to 18 years old. Topics with significant practice variation and those that would improve the quality of patient care were prioritized. Results: The development group identified 59 candidate consensus statements, based on 50 initial proposed topics, that focused on addressing the following high-yield topics: (1) indications and utility, (2) protocol, (3) optimal sedation, (4) grading and interpretation, (5) complications and safety, and (6) outcomes for DISE-directed surgery. After 2 iterations of the Delphi survey and removal of duplicative statements, 26 statements met the criteria for consensus; 11 statements were designated as no consensus. Several areas, such as the role of DISE at the time of adenotonsillectomy, were identified as needing further research. Conclusion: Expert consensus was achieved for 26 statements pertaining to indications, protocol, and outcomes for pediatric DISE. Clinicians can use these statements to improve quality of care, inform policy and protocols, and identify areas of uncertainty. Future research, ideally randomized controlled trials, is warranted to address additional controversies related to pediatric DISE.